Activation of nuclear factor-kappa B accelerates vascular calcification by inhibiting ankylosis protein homolog expression - Zhao, Gexin; Xu, Ming-Jiang; Zhao, Ming-Ming; Dai, Xiao-Yan; Kong, Wei; Wilson, Gerald M.; Guan, Youfei; Wang, Cun-Yu; Wang, Xian (Kidney international, 2012)
Vascular calcification is a major risk factor of cardiovascular mortality, particularly for patients with end-stage renal disease and diabetes. Although chronic inflammation is one of the etiologic factors, the underlying mechanism is not fully understood. To clarify this, we studied how nuclear factor-kappa B (NF-κB) induction, a mediator of inflammation, might promote vascular calcification. Activation of NF-κB by tumor necrosis factor (TNF) promoted inorganic phosphate-induced calcification in human aortic smooth muscle cells. Pyrophosphate (an inhibitor of calcification) efflux to the extracellular matrix was suppressed along with the decreased expression of ankylosis protein homolog (ANKH), a transmembrane protein that controls pyrophosphate efflux of cells. The restoration of ANKH expression in these cells overcame the decreased pyrophosphate efflux and calcification. Tristetraprolin, a downstream product of NF-κB activation, may mediate destabilization of ANKH mRNA as its knockdown by shRNA increased ANKH expression and decreased calcification. Furthermore, a rat chronic renal failure model, with increased serum TNF levels, activated NF-κB and decreased ANKH levels. In contrast, the inhibition of NF-κB maintained ANKH expression and attenuated vascular calcification both in vivo and in vitro. Both human calcified atherosclerotic lesions and arteries from patients with chronic kidney disease had activated NF-κB and decreased ANKH expression. Thus, TNF-activated NF-κB promotes inflammation-accelerated vascular calcification by inhibiting ankylosis protein homolog expression and consequent pyrophosphate secretion.